POLYMORPHISM OF β-LACTOGLOBULIN IN PRAMENKA SHEEP BREED IN BOSNIA AND HERZEGOVINA - A. Rustempašić; A.Dokso; E.Zečević; A. Hodžić; A.Hrković-Porobija; Z.Sarić; E. Miskoska–Milevska; Z. Popovski; M. Brka (Journal of Animal and Plant Sciences, 2018)
The aim of this study was to determinate allele frequency β-lactoglobulin in Pramenka breed sheep in Bosnia and Herzegovina. The DNA was extracted from blood of 283 sheep, collected from four flocks around Sarajevo, Bosnia and Herzegovina. The gene β-lactoglobulin was amplified using polymerase chain reaction – restriction fragment length polymorphism (PCR–RFLP) technique. Two genetic variants (A and B) and three genotypes (AA, AB and BB) of β-lactoglobulin have been identified. Genotype frequencies of β-lactoglobulin were with the following values: AA (0.325), AB (0.445), and BB (0.229), while the frequencies of allele A and B were 0.547 and 0.453 respectively. The highest frequency of genotype AA is present in the location Treskavica (38%), genotype AB in the location Vlašić (52%), while the genotype BB is mostly present in location Bjelašnica (29%). The population of Pramenka breed sheep was in Hardy-Weinberg equilibrium. It is expected that in a future the programs in sheep breeding in Bosnia and Herzegovina certainly would take into account the genetic variants of β-lactoglobulin that could contribute to better production and economic benefit.
Keywords: β-lactoglobulin; genetic polymorphism; Pramenka breed